2021
DOI: 10.1097/md.0000000000026069
|View full text |Cite
|
Sign up to set email alerts
|

Is methicillin-resistant Staphylococcus aureus a common pathogen in ventilation-associated pneumonia?

Abstract: Ventilator-associated pneumonia is a life threatening device related infection in intensive care units. Methicillin-resistant Staphylococcus aureus is considered a common contagious pathogen causing pneumonia and sepsis. To assess the prevalence of S aureus in comparison to other pathogens, and their antibacterial sensitivity profile in ventilator-associated pneumonia. Data regarding ventilator-associated pneumonia of adults admitted to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This is consistent with other reported studies. [15,25] On the other hand, an international retrospective study showed that gram-positive bacteria were the most common isolated microorganisms from COVID-19 patients. Streptococcus pneumonia and S aureus stood at 16.2% each.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other reported studies. [15,25] On the other hand, an international retrospective study showed that gram-positive bacteria were the most common isolated microorganisms from COVID-19 patients. Streptococcus pneumonia and S aureus stood at 16.2% each.…”
Section: Discussionmentioning
confidence: 99%
“…As a primary contributor to nosocomial pneumonia and healthcare-associated (HCA) pneumonia, methicillin-resistant Staphylococcus aureus (MRSA) is linked with significant morbidity and mortality ( 1 , 2 ). MRSA is responsible for 10%–40% of cases of HCA pneumonia, hospital-acquired pneumonia (HAP), and ventilator-associated pneumonia (VAP) ( 3 ). MRSA pneumonia is characterized by a pronounced inflammatory reaction in the lungs, resulting in airway neutrophil influx, loss of alveolar structure, severe pulmonary edema, hemorrhage, and intrapulmonary bacterial proliferation.…”
Section: Introductionmentioning
confidence: 99%